STUDI KOMPARASI TINGKAT EFISIENSI ANTARA BANK ASING DAN BANK SWASTA NASIONAL DI INDONESIA - Riska Laila Maulidah Noor; Paidi Hidayat (Ekonomi dan Keuangan, 2014)
The aim of this research is to measure efficiency between foreign banks and private national banks in Indonesia during the period 2008-2012. The data which is used is a secondary data, collected from financial statements issued by Bank Indonesia.The sampling technique is used in this research is purposive sampling with taking foreign 2 samples of foreign and 2 samples of private national banks. Efficiency measurements in this research using the method of Data Envelopment Analysis (DEA) with the intermediation approach. Input variables used in the study are deposits, assets, and labor costs, while the output variables are loans or finance and revenue.The results of this research showed that the bank reached a level of efficiency of 100 percent during the period 2008-2012 are Citibank,NA, and Bank Danamon with the average achievement level of efficiency between foreign banks and private national banks was 92.4% and 98%.Keywords: Efficiency, Foreign Banks and Private NationalBanks, Data Envelopment Analysis